Hubungan ketuban pecah dini dengan kadar leukosit bayi baru lahir di BLUD RS H.Boejadin Pelaihari Kabupaten Tanah Laut - Sri Sumartini; Sujiyatini Sujiyatini; Dwiana Estiwidani (Poltekkes Kemenkes Yogyakarta, 2012)
Infant modality rate in Indonesia was still high, one of its factors was infection. Mothers with risk of infection occurs and premature amniotic rupture involved into clinical curio amnion is as well as associated with neonatal infection. indicators rate occurrence of the initial processes infection newborn baby was leukocytosis. This study was to know the relationship between prevalence rate and premature amniotic rupture with leukocytosis levels of newborn infant in Public Service Area H. Boejasin Pelaihan Hospital, Tanah Laut in 2011. Analytic survey with cross-sectional approach. Population was 947 partum, with Simple Random Sampling techniques found 350 samples. Data secondary data of medical record. It used Chi- Square test with 95% Cl. Results: The leukocytes levels of newborn infant with premature amniotic rupture mostly not in the normal limit 36,28%. Data analysls result showed that there was significant relationship between premature amniotic rupture with leukocytes levels of newborn infant (X count = 25.212 with p-value = 0.000), and RP:2.79